2018
DOI: 10.1371/journal.pone.0208530
|View full text |Cite
|
Sign up to set email alerts
|

Development of a recombinase polymerase based isothermal amplification combined with lateral flow assay (HLB-RPA-LFA) for rapid detection of "Candidatus Liberibacter asiaticus"

Abstract: Huanglongbing (HLB) or citrus greening is highly destructive disease that is affecting the citrus industry worldwide and it has killed millions of citrus plants globally. HLB is caused by the phloem limited, Gram negative, non-culturable, alpha-proteobacterium, ‘Candidatus Liberibacter asiaticus’. Currently, polymerase chain reaction (PCR) and real time PCR have been the gold standard techniques used for detection of ‘Ca. L. asiaticus’. These diagnostic methods are expensive, require well equipped laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 40 publications
(44 reference statements)
0
45
0
Order By: Relevance
“…The RPA-LFD method has been applied for the detection of many pathogens, including goose parvovirus [33], Burkholderia mallei [34], Trichinella spp. [35], Mycoplasma bovis [36], Candidatus Liberibacter asiaticus [37], Pasteurella multocida [38] and Phytophthora soja [39].…”
Section: Introductionmentioning
confidence: 99%
“…The RPA-LFD method has been applied for the detection of many pathogens, including goose parvovirus [33], Burkholderia mallei [34], Trichinella spp. [35], Mycoplasma bovis [36], Candidatus Liberibacter asiaticus [37], Pasteurella multocida [38] and Phytophthora soja [39].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding maceration, several reagents have been applied to prepare plant crude macerates that can be directly utilized in RPA reaction. Those reagents include TE buffer (Ahmed et al 2018), NaOH (Karakkat et al 2018;Qian et al 2018), standard ELISA grinding buffer (Miles et al 2015), and commercial buffers GEB (Kumar et al 2018), GEB 2 (Miles et al 2015;Li et al 2017), GEB 4 (Zhang et al 2014) and AMP1 (Kalyebi et al 2015;Ghosh et al 2018) from Agdia, Inc. In contrast, our investigation on standard ELISA grinding buffer revealed that no component of the buffer was essential for obtaining RPA amplification.…”
Section: Discussionmentioning
confidence: 82%
“…Crude macerates have been prepared with different buffers. Ready-to-use buffers from Agdia, Inc. such as GEB , GEB 2 (Miles et al, 2015;Li et al, 2017), GEB 4 (Zhang et al, 2014) and AMP1 (Kalyebi et al, 2015;Ghosh et al, 2018) have been utilized. Similarly, NaOH (Karakkat et al, 2018;Qian et al, 2018), standard ELISA grinding buffer (Miles et al, 2015), and TE buffer (Ahmed et al 2018) have also been used for maceration.…”
Section: Introductionmentioning
confidence: 99%